Analysis of Intra-Abdominal Pressure in Obstructive and Perforative Lesions of Gastro-Intestinal Tract - Kidwai, Roman; Baral, Ravi Kumar; Sharma, Anup (Journal of Nepalgunj Medical College, 2018)
Introduction: Abdominal Compartment syndrome is an emerging problem in surgical patients with significant mortality reaching up to 100% in untreated patients. Intra abdominal hypertension (IAH) and abdominal compartment syndrome is common finding in traumatic and critically ill surgical patients. There are sporadic case reports in literature of intra abdominal hypertension & abdominal compartment syndrome in general surgical patients, particularly in obstructive and perforative diseases of gastrointestinal tract (GIT). This study was done to know the pattern of intraabdominal pressure (IAP) and effect of intra abdominal hypertension (IAH) in obstructive and perforative lesions of gastrointestinal tract. Materials and Method: A total number of 145 cases were included between November 2016 to October 2017. These patients were from the department of Suregery, Nepalgunj Medical College, who underwent Surgery due to the Intestinal Obstruction or perforation. Result: There were total 145cases. The incidence of IAH in patients with intestinal obstruction and perforation peritonitis at presentation was 68.27%. 65 (66.32%) out of 98patients with perforation peritonitis had IAH and 34 (72.34%) with intestinal obstruction among 47 had IAH before surgery. There were 2.12% patients with abdominal compartment syndrome (ACS) in obstruction and 3.06% in perforation; ACS was highest amongst traumatic perforation population accounting for 13.33% of traumatic cases. There was statistically significant derangement (p-value<0.05) of organ function with raised IAP which showed marked improvement following surgery. Four patients died, all these patients had ACS at the time of presentation. Conclusion: IAH is a significant entity in obstructive and perforative lesions of GIT. ACS can occur in obstructive and perforative lesions of GIT with significant mortality.